Pemetaan Geologi Dalam Mengungkap Potensi Sumber Daya Alam Desa Bonedaa, Suwawa Selatan, Gorontalo - Pade, Dwi Ziana Jamila; Akase, Noviar; Hutagalung, Ronal; Dachi, Mirdayanti; Mokodompit, I Gede Wahyu; Tangkudung, Latifa; Ente, Amargio Saputro; Rahman, Adisty S.; Puhi, Rian; Yani, Lisra; Putra, Moh. Bahrul Zaman Momidu; Nurahman, Ikwan (Universitas Negeri Gorontalo, 2025)
The community in Bonedaa Village and its surroundings possesses untapped natural resource potential. This community service aims to enhance public understanding of local geological conditions and natural resources through participatory geological mapping. The methods applied include field education, group discussions, and training on rock and geological structure identification. The results show an increased awareness among residents regarding local rock types, construction material potential, and geological hazards such as landslides and erosion. Participatory mapping produced a simplified geological map useful for village-level planning and decision-making. This activity demonstrates that geological approaches can contribute directly to sustainable resource management and disaster risk reduction. The outcomes are significant in promoting community resilience and independence based on local potential.